2021
DOI: 10.3389/fped.2021.679597
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel HSD17B4 Heterozygous Mutations in Association With D-Bifunctional Protein Deficiency: A Case Report and Literature Review

Abstract: Background: D-Bifunctional protein deficiency (D-BPD) is an autosomal recessive disorder caused by peroxisomal β-oxidation defects. According to the different activities of 2-enoyl-CoA hydratase and 3-hydroxyacyl-CoA dehydrogenase protein units, D-bifunctional protein defects can be divided into four types. The typical symptoms include hypotonia and seizures. The gene that encodes D-BP was HSD17B4, which is located in chromosome 5q23.1.Case Presentation: We report the first case of D-BPD in a Chinese patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
3
0
3
Order By: Relevance
“…On chromosome 5q23.1, HSD17B4 encodes a bifunctional enzyme that is involved in the peroxisomal beta‐oxidation pathway for both straight‐chain and 2‐methyl‐branched‐chain fatty acids. Mutations in this locus lead to a distinct neurological condition due to the inherent defect of beta‐oxidation 42 . While no specific studies of HSD17B4 have been reported in MS or COVID‐19 thus far, peroxisome pathways are disturbed in each of these two disorders 43,44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On chromosome 5q23.1, HSD17B4 encodes a bifunctional enzyme that is involved in the peroxisomal beta‐oxidation pathway for both straight‐chain and 2‐methyl‐branched‐chain fatty acids. Mutations in this locus lead to a distinct neurological condition due to the inherent defect of beta‐oxidation 42 . While no specific studies of HSD17B4 have been reported in MS or COVID‐19 thus far, peroxisome pathways are disturbed in each of these two disorders 43,44 …”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this locus lead to a distinct neurological condition due to the inherent defect of beta-oxidation. 42 While no specific studies of HSD17B4 have been reported in MS or COVID-19 thus far, peroxisome pathways are disturbed in each of these two disorders. 43,44 A total of 24 protein-coding genes were implicated by the analysis of molecular relationships within the reconstructed pathways mediating the synergistic link between MS and COVID-19.…”
Section: T a B L E 1 Causal Associations Between Ms And Covid-19mentioning
confidence: 99%
“…У человека идентифицированы две ацил-КоА-оксидазы с различной субстратной специфичностью На рубеже XX в. был описан новый фермент пероксисомального β-окисления, названный D-бифункциональным белком (D-ВР) с активностью еноил-КоА-гидратазы и 3-гидроксиацил-КоА-дегидрогеназы, в первую очередь реагирующий с α-метиловыми жирными кислотами, DBP представляет собой гомодимерный фермент с субъединицами 79 кДа и содержит три функциональных домена: 3-гидроксиацил-КоА-дегидрогеназу, 2-еноил-КоА-гидратазу и домен, подобный белку-носителю стерола 2. Три функциональные единицы DBP необходимы для разложения жирных кислот с очень длинной цепью (VLCFA), α-метильных жирных кислот с разветвлённой цепью и промежуточных продуктов желчных кислот, таких как DHCA и THCA [11].…”
Section: клинико-патогенетические механизмыunclassified
“…Все три типа имеют сходную клиническую картину, однако различаются по степени тяжести. Так, пациенты с дефицитом I типа демонстрировали самые тяжёлые симптомы со средней продолжительностью жизни в 6,9 месяца, в то время как у пациентов со II и III типами продолжительность жизни составила 10,7 и 17,6 месяцев соответственно [11].…”
Section: клинико-патогенетические механизмыunclassified
“…Diskussion Die D-bifunktionelle Protein-Defizienz ist eine seltene autosomal rezessive Erbkrankheit 4 5 . Analog zu unserem Fall sind typische Befunde eine Muskelhypotonie, zerebrale Anfälle und kraniofaziale Pathologien.5 Das klinische Bild variiert 6 7 8 9 . In der Literatur finden sich allerdings keine Berichte über Begleitthrombosen wie im vorgestellten Fall.…”
unclassified